Achievement motivation as a predictor of historical empathy: a study of social studies university students - Mohamed Ali Nemt-allah; Hamed Samy Ghareib; Elsayed Atef El-Hashimi; Mashael Nasser Al-Dosari; Mohamed Sayed Abdellatif; Tawfik Mahmoud Soliman; Ashraf Ragab Ibrahim (Institute of Advanced Engineering and Science, 2026)
This study investigated the predictive relationship between achievement motivation and historical empathy among social studies university students. Using the achievement motives scale-revised (AMS-R) and the historical empathy scale-adult form (HES-AF), data were collected from 428 Egyptian university students aged 18-24 from education faculties at Al-Azhar University. Correlation analyses revealed significant positive relationships between achievement motivation dimensions (hope of success and fear of failure) and all historical empathy components (cognitive, affective, and behavioral). Multiple regression analysis demonstrated that achievement motivation significantly predicted historical empathy, F(2, 425)=86.035, p<.001, explaining 28.8% of the variance. Hope of success emerged as the primary predictor (β=.478, p<.001), with approximately four times the predictive strength of fear of failure (β=.109, p=.018). These findings suggest that approach-oriented achievement motivation, particularly hope of success, is crucial in fostering empathetic understanding of historical content. The results provide theoretical insights into the psychological mechanisms underlying historical empathy and offer practical guidance for educators seeking to enhance empathetic engagement in social studies education through motivation-focused pedagogical approaches.